Опыт применения привлекающих веществ для изучения мух-саркофагид (Diptera, Sarcophagidae) - Вервес, Ю.Г. (Вестник зоологии, 1973)
Various substances were tested in the Kanev reservation for some years to find attractive ones for insects. The steamed Astragalus danicus L a t r. and 1% solution of hephaep¬hytinum in water proved to be the most effective food attractants for Sarcophagidae. Using these substances 2446 Sarcophagidae individuals of 20 species are caught and the peculi¬arities of their seasonal dynamics are studied.